Evaluation of Academic Atmosphere Formation in Islamic Junior High School Through Digital Learning System - Iskandar Tsani; Asna Lu'Lu'in Nisa'; Sufirmansyah Sufirmansyah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to evaluate the formation of an academic atmosphere for students in MTsN 1 Kediri City through a digital learning system. This article is written based on field research with a qualitative approach of evaluative research type, using the CIPP model evaluation framework (context, input, process, and product). Data were collected through personal interviews, observation, and documentation. Data is analyzed interactively, including the stages of data reduction, data presentation, and conclusions. Triangulation of credibility, transferability, dependability, and confirmability is carried out to ensure the validity of data obtained from informants. This article concludes: 1) Context: madrasah has a good understanding of the digital learning system. The legality of the program is in accordance with the circular issued by the government. The environment strongly supports digital learning. The purpose of the program is to train students' in critical and innovative thinking. 2) Input: Human resources in the madrasah collaborate well in the implementation of digital learning. Supporting infrastructure facilities have been optimally met. The source of funds comes from the central government and there is internet quota assistance to students. 3) Process: the implementation of learning is carried out completely online using Madrasah E-Learning and other digital applications such as WhatsApp, Google Form, Youtube, and so on. Learning monitoring is carried out every month by the Head of Madrasah and the IT team. Some of the obstacles experienced in the implementation of digital learning include the variety of teachers' ability to utilize IT, fluctuating internet signals, various gadget storage capacities, and students' lack of understanding regarding online learning. 4) Product: the academic atmosphere formed can be seen from a number of indicators. The aspect of the learning atmosphere in class gets a score of 80% (high). The aspect of relations between class citizens received a score of 86% (high). The aspect of teaching and learning activities scored 93% (very high). The discipline aspect of students in the classroom gets a score of 70% (high). The online learning aspect scored 73% (high).